Surgical management for dystonia: Efficacy of deep brain stimulation in the long term - Kamel, Walaa A.; Majumdar, Pritam; Matis, Georgios; Fenoy, Albert J.; Balakrishnan, Shankar; Zırh, Tahsin Ali; Çevik, Aslıhan; Tomar, Amit Kumar; Ouerchefani, Naoufel (MDPI AG, 2021)
Introduction: Dystonia is a movement disorder substantially affecting the quality of life. Botulinum Neurotoxin (BoNT) is used intramuscularly as a treatment for dystonia; however, not all dystonia patients respond to this treatment. Deep brain stimulation (DBS) is an established treatment for Parkinson’s disease (PD) and essential tremor, but it can help in dystonia as well. Objectives: We studied a total of 67 dystonia patients who were treated with DBS over a period of 7 years to find out the long-term efficacy of DBS in those patients. First, we calculated patient improvement in post-surgery follow-up programs using the Global Dystonia Severity scale (GDS) and Burke–Fahn–Marsden dystonia rating scale (BFMDRS). Secondly, we analyzed the scales scores to see if there was any statistical significance. Methods: In our study we analyzed patients with ages from 38 to 78 years with dystonia who underwent DBS surgery between January 2014 and December 2020 in four different centers (India, Kuwait, Egypt, and Turkey). The motor response to DBS surgery was retrospectively measured for each patient during every follow-up visit using the GDS and the BFMDRS scales. Results: Five to 7 years post-DBS, the mean reduction in the GDS score was 30 ± 1.0 and for the BFMDRS score 26 ± 1.0. The longitudinal change in scores at 12 and 24 months post-op was also significant with mean reductions in GDS and BFMDRS scores of 68 ± 1.0 and 56 ± 1.0, respectively. The p-values were <0.05 for our post-DBS dystonia patients. Conclusions: This study illustrates DBS is an established, effective treatment option for patients with different dystonias, such as generalized, cervical, and various brain pathology-induced dystonias. Although symptoms are not completely eliminated, continuous improvements are noticed throughout the post-stimulation time frame.
Keywords: Burke–Fahn– Marsden Dystonia Rating Scale (BFMDRS); Deep Brain Stimulation (DBS); GLOBAL DYSTONIA SEVERITY Scale (GDS); Globus Pallidus Interna (Gpi); Subthalamic Nucleus (STN)